(untitled) (diségno, 2025)
Drawing, understood as a language, is inherently ambiguous: every mark can be misinterpreted, reinterpreted, or manipulated. Starting from Paul Ricoeur’s reflection on the link between interpretation and the possibility of misunderstanding, this essay investigates architectural drawing as a non-neutral device, shaped by cultural conventions, biases, and social contexts. Through the analysis of historical examples –from the accusations of espionage against Aleksandr Alekhine, triggered by the misunderstanding of chess score sheets, to the controversial reception of Frank Lloyd Wright’s Masieri Memorial project– it highlights how drawing can become a tool for ideological misinterpretation. A close reading of Jean-Jacques Lequeu’s drawings further reveals how seemingly geometric inaccuracies disclose a more complex rhetorical and symbolic intention. The article proposes a classification of ambiguities into four categories: technical, epistemic, rhetorical, and perceptual. The latter is illustrated through the phenomenon of multistable images (Kippbilder), which underline the inherent instability of human perception. In conclusion, the essay argues that the ambiguity of drawing, far from being a mere source of error, constitutes a vital element of its creative and hermeneutic potential, encouraging a more critical and conscious reading of architectural representation.